Second law analysis of a disturbed flow in a thin slit with wall suction or injection - Kamisli, Fethi (Pergamon-Elsevier Science Ltd, 2008)
Fully-developed laminar flow in a horizontal thin slit having plates at different temperature is considered for the case of lower plate movement and/or the pressure gradient-and-upper plate movement. The flow under these conditions is analyzed in terms of entropy generations as function of the Prandtl number, the Eckert number, cross-flow Reynolds number and dimensionless temperature difference. In this context, the governing equations for distributions of temperature, the dimensionless entropy generation number and Bejan number are analytically derived with the aid of expressions for velocity distributions. The effect of each parameter on the temperature and the entropy generation are investigated by varying one of the parameters and keeping the rest of them constant for each flow case. The effects of viscous dissipation, rates of mass suction/injection and dimensionless temperature differences on the fluid temperature and entropy generation are examined. The magnitudes of mass suction and/or injection have a large influence on the temperature profile of the fluid. It is observed that the Prandtl number and the Eckert number affect fluid temperature in similar way. It is found that an increase in values of the cross-flow Reynolds number (mass suction/injection) enhances the entropy generation in boundary layer. The velocity profiles are found to be in agreement with the distributions of the dimensionless entropy generation number (Ns) for two flow cases. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: second law analysis; entropy generation; wall suction/injection